Unleashing Uncharted Horizons: The Parallel Evolution of AI and Historic Technological Shifts - Niham, Dutta (Pandawan Sejahtera Indonesia, 2023)
The transformative impact of technological innovation in warfare through historical examples of Tanks and Airplanes emerging from World War I. It highlights the swift evolution from invention to weaponization, emphasizing the potential for unexpected consequences. Drawing parallels with the nascent AI technology, the abstract discusses its uncertain role in shaping the future, including its current applications in warfare and governance. It underscores the growing influence of AI across sectors, especially in the military domain with instances like Ukraine. Amid a global shift towards AI adoption, led by major nations, the abstract underscores the emergence of a potentially perilous AI technology race, raising concerns about its capabilities and vulnerabilities, including scenarios of rogue actions with catastrophic implications.